Oral Examinations: Going Back to our Academic Roots - Heaton, Steve (Bulletin for the study of religion, 2024)
The Buzz examines scholarly topics in light of present-day concerns and challenges. This edition centers on the sometimes-mundane nature of written examinations and how switching to oral examinations may be beneficial to students and professors. Editorial assistant Steve Heaton speaks from his experience as a teaching assistant and finds refreshing a recent piece by Krista Dalton, Assistant Professor of Religious Studies at Kenyon College in Gambier, Ohio. The piece is from the scholarly blog "Ancient Jew Review," titled, "How I Give Oral Finals." Our team agrees with Heaton as we hear more and more Bulletin readers’ anxious about grading in the age of artificial intelligence and large learning models.